2022
DOI: 10.1177/10499091211052853
|View full text |Cite
|
Sign up to set email alerts
|

The Differences and Perspectives Between Elderly Individuals and Their Surrogates Regarding End-of-Life Care: A Mixed Methods Study

Abstract: Background: Family members often take the place of decision-making for elderly individuals. Previous studies showed that family members could not predict elderly individuals’ thoughts about end-of-life care. Objectives: The aims are to understand the differences and perspectives between elderly individuals and surrogates regarding end-of-life care. Design: A mixed methods study comprising a cross-sectional survey and field notes analysis. Setting: Two geriatric wards in a veterans hospital located in northern … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 46 publications
1
1
0
Order By: Relevance
“…The participants in the present study rated CPR as the least desirable medical treatment, a finding consistent with those of several other studies [ 10 , 18 , 19 , 20 ]. With the promotion of palliative care in Taiwan, most older adults no longer want to receive ineffective medical treatments such as CPR, and they value their hospice rights.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The participants in the present study rated CPR as the least desirable medical treatment, a finding consistent with those of several other studies [ 10 , 18 , 19 , 20 ]. With the promotion of palliative care in Taiwan, most older adults no longer want to receive ineffective medical treatments such as CPR, and they value their hospice rights.…”
Section: Discussionsupporting
confidence: 92%
“…A study analyzing Taiwan’s health insurance database reported a significant drop in the proportion of older adults with dementia receiving CPR, from 31% in 2010 to 15% in 2013 [ 21 ]. A mixed study noted considerable agreement between an elderly Taiwanese population and their surrogates regarding their refusal to undergo CPR in end-of-life care [ 18 ]. The end-of-life care of older adults does not require CPR, a fact that has gained the attention of most Taiwanese.…”
Section: Discussionmentioning
confidence: 99%